The Effect of Mosaic Method Using Grains and Paper on Fine Motor Development of Children Aged 5-6 Years: A Pre-Experimental Study at Raden Patah Kindergarten Surabaya - Rahma Annisa'; Aida Novitasari; Joko Suwito; Sari Luthfiyah (International Journal of Advanced Health Science and Technology, 2026)
Fine motor development in preschool children is a fundamental element that underpins independence, readiness to learn, and future academic success. However, delayed development in this area is still commonly found, requiring stimulation that is not only educationally appropriate but also enjoyable for children. One approach that is considered effective is the mosaic method, an art activity of arranging tesserae into visual works. This study was conducted to evaluate the effectiveness of using mosaics made from grains and paper in improving fine motor skills in children aged 5 to 6 years. This study applied a pre-experimental research design through a one-group pretest-posttest approach. A total of 30 children were selected as participants using simple random sampling. During a two-week period, the participants received an intervention in the form of mosaic-making activities six times. Data collection was carried out using observation instruments that had been tested for validity and reliability. Initial evaluation results show that 60% of children are at the developing as expected (DaE). However, after routine stimulation, there was a significant jump in performance, with 80% of children achieving the category of very well developed (VwD). Statistical analysis using the Wilcoxon test reinforced these findings with a p-value of 0.000 (p < 0.05) and an effect size of 0.875, which is classified as a very strong impact. This scientifically proves that the mosaic method using natural materials such as grains and paper has a major positive impact on honing children's eye-hand coordination. Therefore, this method is highly recommended as an effective, economical, and recreational alternative stimulation medium in early childhood education systems and home care patterns.